SPEAKING CHALLENGE, DOES PRONUNCIATION AS THE ATTRIBUTE OF FLUENCY? - Annisa Annisa; Wariyati Wariyati (Journey: Journal of English Language and Pedagogy, 2023)
Speaking skill is a difficult aspect for language students. In speaking, there are things that need to be considered such as pronunciation of vocabulary. However, students still have difficulty in articulating many words as the indicator of fluency. This case also brings many assumptions in vocabulary pronunciation. The variety of speaking difficulties faced by students of grade VIII in MTs S Ummi Lubuk Pakam was being the main aim. A qualitative descriptive method that presents findings and research results qualitatively was implemented. The voice recordings used as the data and the supporting finding was gotten from the observation result, then it was clarified through the interviews transcript. This analysis found that in speaking English accurately, students had not mastered the phonological rules and they did not know the various sounds or pronunciations. The evidence also proven that the stress, intonation and pitch become the big problems in English utterances. The low quality of pronunciation brings conclusion about students’ factors in low speaking competency